Гудвіл як критерій репутації компанії - Полозова, Т. В.; Колісниченко, Я. А. (ХНУРЕ, 2015)
The concept of goodwill is considered . Basic methods of measurement of goodwill are analyzed. Analyzed the areas in which the goodwill is applied. The benefits of a positive reputation are considered.
Keywords: гудвіл; ділова репутація компанії; оцінка репутації компанії; goodwill; інвестиційна привабливість